Determinación serológica en ca, p, mg, fe en bovinos productoras de leche en Ashpa Corral, parroquia Guanujo, provincia Bolívar - González Núñez, Jaime Fernando (2021)
The demand for increasing global food production added to the technification and the accelerated pace of progress of current farms; means that livestock must withstand high production pressures increasing nutrient requirements, has been demonstrated with clinical and productive evidence, the important metabolic role of minerals in the healthy and productive animal, as it has also been defined what mineral element and percentage of it is required for the normal functioning of the organism. The objectives for this research were: To determine the serological level in Ca, P, Mg, Fe in milk producers in Ashpa corral; Compare mineral levels (Ca, P, Mg, Fe) in blood serum in the cattle under study with the reference values according to tables for dairy cattle; Identify the most deficient minerals in the study area. Twenty-five lacing adult cattle were sampled for the purpose of determining whether there is a relationship between aberrant appetite and mineral deficiency. The variables evaluated were: Weight (CP) finding a value average of 412.00kg; Age (E) by dentition being an average of 5.52 years; Number of lactations (NL) the mean was 3 lactations; Daily milk production (PDL) the average production per day was 6 liters; Third of lactation (TL) the middle third of lactation was 2; Gestation (PRÑ) we find 36% pregnancy vs 64% weightlessness by rectal palpation; Body Condition (BCI) was determined an average of 3.32; Serum Calcium Concentration (CCaS) by photometry the mean was 9.96 mg/dl; Blood Phosphorus Concentration (CFS) there were concentrations below the range reaching deficiencies of this mineral in some animals <3.1mg/dl, being the average of 3.52mg/dl; Serum Magnesium Concentration (CMgS) some cases of hypermagnesemia were evidenced >2.4mg/dl being the mean of 2.36mg/dl; in serum iron (CFeS) the mean was 133.92 ug/dl, iron deficiencies were found in adult cows; these results allow us to conclude the absence of a direct relationship between the deficiency or excess of these minerals studied at the serum level and the suffering of aberrant or pica appetite.